Declinol, a Complex Containing Kudzu, Bitter Herbs (Gentian, Tangerine Peel) and Bupleurum, Significantly Reduced Alcohol Use Disorders Identification Test (AUDIT) Scores in Moderate to Heavy Drinkers: A Pilot Study - Kushner, Steven (2013)
It is well established that inherited human aldehyde dehydrogenase 2 (ALDH-2) deficiency reduces the risk for alcoholism. Kudzu plants and extracts have been used for 1,000 years in traditional Chinese medicine to treat alcoholism. Kudzu contains daidzin, which inhibits ALDH-2 and suppresses heavy drinking in rodents. Decreased drinking due to ALDH-2 inhibition is attributed to aversive properties of acetaldehyde accumulated during alcohol consumption. However not all of the anti-alcohol properties of diadzin are due to inhibition of ALDH-2. This is in agreement with our earlier work showing significant interaction effects of both pyrozole (ALDH-2 inhibitor) and methyl-pyrozole (non-inhibitor) and ethanol’s depressant effects. Moreover, it has been suggested that selective ALDH 2 inhibitors reduce craving for alcohol by increasing dopamine in the nucleus accumbens (NAc). In addition there is significant evidence related to the role of the genetics of bitter receptors (TAS2R) and its stimulation as an aversive mechanism against alcohol intake. The inclusion of bitters such as Gentian & Tangerine Peel in Declinol provides stimulation of gut TAS2R receptors which is potentially synergistic with the effects of Kudzu. Finally the addition of Radix Bupleuri in the Declinol formula may have some protective benefits not only in terms of ethanol induced liver toxicity but neurochemical actions involving endorphins, dopamine and epinephrine. With this information as a rationale, we report herein that this combination significantly reduced Alcohol Use Disorders Identification Test (AUDIT) scores administered to ten heavy drinkers (M=8, F=2; 43.2 ± 14.6 years) attending a recovery program. Specifically, from the pre-post comparison of the AUD scores, it was found that the score of every participant decreased after the intervention which ranged from 1 to 31. The decrease in the scores was found to be statistically significant with the p-value of 0.00298 (two-sided paired test; p-value = 0.00149 for one-sided test). Albeit this being a small pilot, we are encouraged about these significant results, and caution any interpretation until larger controlled studies are executed.